Foraging by the omnivorous crab Pachygrapsus transversus affects the structure of assemblages on sub-tropical rocky shores - Christofoletti, Ronaldo A.; Murakami, Valeria A. [UNESP]; Oliveira, Diogo N. [UNESP]; Barreto, Rodrigo E. [UNESP]; Flores, Augusto A. V. (Inter-research, 2010)
The roles of herbivory and predation in determining the structure and diversity of communities have been tested across most intertidal systems. In contrast, the importance of omnivorous consumers remains untested in many rocky shore communities. We tested the role of a small omnivorous crab in an intertidal food web on rocky shores of the sub-tropical southwest Atlantic. Exclusion of the grapsid crab Pachygrapsus transversus in the field resulted in significant changes in the abundance of functional groups in the sublittoral fringe of sheltered shores, where the dominant cover changed from a suite of macroalgae to an assemblage of filter-feeding animals (ascidians, sponges, mussels). In contrast, limpets, whelks, large crabs and fish did not significantly affect community composition of the assemblage. To examine the omnivorous feeding pattern of P. transversus, we did laboratory experiments to test its foraging behaviour among animal and algal groups. The crab showed selective behaviour, preferring invertebrate groups to macroalgae, and opportunistic behaviour among types of prey within those major groups. According to our results, the role of slow-moving and large fast-moving consumers is apparently negligible compared to the effect of an omnivorous consumer. P. transversus plays an important role in determining the intertidal community composition on these subtropical rocky shores, causing changes in the balance of functional groups and controlling invasive species.
Keywords: Omnivory; Predation; Community ecology; Top-down control; Functional groups; Food web; Foraging behaviour